The Application of Sinclair & Coulthard Verbal and Nonverbal Model Analysis in Teaching Descriptive Text - Deviara Lestari; Laura J R Sitorus; Nazwa Inaya Sani; Ribka Manurung (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aimed to analyze the application of Sinclair and Coulthard’s verbal and nonverbal model in teaching descriptive text to 11th-grade students. Using a qualitative descriptive approach, this research was conducted through Classroom Discourse Analysis based on a recorded English teaching session at MAS Darul Azhariyun. The data consisted of the teacher’s and students’ verbal and nonverbal interactions, transcribed and categorized according to Sinclair and Coulthard’s (1975) framework, including exchange, move, and act. The findings revealed that the classroom interaction was predominantly teacher-centered, structured through the Initiation–Response–Feedback (IRF) sequence. However, despite the teacher’s dominant role, interactive moments occurred through group discussions, presentations, and questioning sessions that encouraged student participation. Nonverbal communication such as gestures, facial expressions, and tone were found to reinforce meaning, support comprehension, and maintain engagement. The study identified that while students’ responses were often short, the teacher’s scaffolding and feedback effectively maintained communicative flow and ensured lesson coherence. These findings suggest that the integration of verbal and nonverbal discourse based on Sinclair and Coulthard’s model contributes to clearer instructional structure, improved classroom interaction, and increased student attentiveness. It also highlights the potential of discourse analysis as a reflective tool for teachers to evaluate communication strategies and promote more interactive, meaningful language learning environments.